Microscopic study on the development of biofilm by staphylococcus aureus on prosthetic device (Catheter) - Mohd Azam Khan Goriman Khan; Che Nor Zarida C. S.; Fauziah O. (2011)
Staphylococcus aureus (S. aureus) is a common cause of biofilm-mediated prosthetic device-related infection. Bacteria that adhere to implanted medical devices or damaged tissue can encase themselves in an extracellular polymeric substance (EPS) and form a slimy layer known as a biofilm. Formation of these sessile communities can become the cause of persistent and chronic bacterial infections. The purpose of this study was to investigate the morphology of in vitro biofilm formation for duration of time using live cell imaging and scanning electron microscopy. S. aureus ATCC 12600 was cultivated in Luria Bertani (LB) broth and diluted with freshly prepared LB broth for overnight (16-18 hours) to achieve standardized 108 CFU/ml cell suspensions. Cell suspension of S. aureus was inoculated into glass bottom petri dish and incubated under live cell imaging for 10 hours. At various times of incubation (day 1, 9, 15 and 17), the catheters that were incubated with S. aureus were collected and then processed for morphology analysis using scanning electron microscopy. Microscopy study of S. aureus biofilm formation in vitro suggests that the pattern of development involves initial attachment to a solid surface, the formation of microcolonies and finally differentiation of microcolonies into exopolysaccharide-encased as a matured biofilm. In conclusion, the microscopic study of S. aureus ATCC 12600 biofilm may be useful for morphological identifiers in classifying bacteria biofilms.